PELATIHAN TEKNIK PERMAINAN TRADISIONAL KEPADA GURU SEKOLAH DASAR DI RANTING V KECAMATAN PASEH KABUPATEN BANDUNG - Prayogi Nurfauzan (LPPM Universitas Islam 45, 2023)
This community service is motivated by the presence of elementary school teachers who are confused and lack understanding about various traditional game techniques, as well as implementing them in education and learning at the elementary school level. Therefore, the purpose of this community service is to provide understanding and skills to elementary school teachers in developing various traditional game techniques in elementary schools. The methods employed in this training include training sessions, question and answer sessions, discussions, practical exercises, and mentoring for elementary school teachers to develop traditional game techniques that can be implemented in teaching and education at the elementary school level. This community service results in an improvement in the understanding and skills of elementary school teachers in developing various traditional game techniques that can be implemented in teaching and education at the elementary school level. Thus, this community service concludes that training activities, question and answer sessions, discussions, practical exercises, and mentoring can enhance the understanding and skills of elementary school teachers in developing various traditional game techniques to improve the quality of education in elementary schools.